Pengaruh Harga Bahan Pangan Terhadap Inflasi Di Indonesia - Octaviana Helbawanti; Wahyu Adhi Saputro; Amalia Nadifta Ulfa (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2021)
AbstractThis study aimed to analyze the effect of food prices on the development of inflation in Indonesia. Indonesia's inflation showed a declining pattern in 2017 to 2021. An analysis of the effect of food prices on inflation is needed to evaluate changes in food prices that cause and contribute to inflation. Food prices fluctuate in the midst of the Covid-19 pandemic in 2020 to 2021 because regional restrictions and mobility can affect the distribution process and availability of food ingredients. Food consumption had a fairly large proportion of total household consumption in developing countries, so changes in food prices would have an impact on economic conditions through demand and supply mechanisms. The analytical method used was multiple linear regression. The data used in the multiple linear regression analysis was secondary data consisting of food prices, namely rice, chicken meat, beef, chicken eggs, shallots, garlic, red chilies, cayenne pepper, cooking oil, granulated sugar and inflation for the July period. 2017 to July 2021. The results of the analysis explained that food ingredients shallots, rice, beef, and cooking oil had a significant effect with a negative coefficient direction on inflation, namely deflation tends to occur in food price movements. Garlic, chicken meat, and sugar had a positive effect on increasing inflation.Keywords: Price, Inflation, Commodity